Numerical modeling of Amasra and Fatsa tsunamis in the Black Sea - Şahin, Esra. (Thesis (M.S.) - Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2013., 2013)
Turkey, a country of frequent earthquakes and with a coastline of 8333 km, is also exposed to the tsunamis, resulting in material loss for the country and its neighbors (Altınok, 1999). Many new investigations have been performed for the tsunami research of the Black Sea region. According to historical data, there have been 26 tsunamis in the Black Sea since the first century; three of which occurred on the Turkish coast. Nine of these tsunamis occurred in the twentieth century (Altınok and Ersoy, 2000). Examining tsunami history and analyzing recent studies in the Black Sea will be crucial tasks for understanding tsunami generation and protecting coastal populations at risk. Two historical tsunamis in the Black Sea have been investigated in this study, employing models obtained from the studies of each event: the Fatsa Tsunami, triggered by the Erzincan Earthquake (Ms=8.0, on 26 December 1939); and the Amasra Tsunami, triggered by the Bartın Earthquake (Ms=6.6, on 3 September 1968). Seismic source parameters of Erzincan and Bartın Earthquakes were investigated on the based of literature and data available for tsunami modeling purposes. In the study, tsunami models from two earthquakes occurred in sea and on land were generated by the NAMIDANCE Tsunami Simulation and Visualization code, using the seismic source parameters. In the Black Sea region, tsunami impact areas were presented by calculating tsunami arriving time, generation of wave, wave propagation and height of wave based on numerical simulation. Furthermore this research compared previously existing tide gauge records from the North Black Sea, thought to be from the Fatsa Tsunami, with the results obtained from the tsunami models using numerical methods and sufficient agreement was found. For this reason, the available instrumental records of water surface fluctuations were digitized by TESEO (Turn the Eldest Seismograms into the Electronic Original Ones) software (Pintore et al., 2005). The tsunami waves generated from Erzincan Earthquake approaches the north coast between 40 min and 2.5 hours later. At the south coasts, maximum wave height is 0.34 m between Ordu and Fatsa towns. In addition, the Amasra Tsunami was investigated in detail using tsunami model methodology and was evaluated its effects on the coasts of the Black Sea Region. Amasra Tsunami modeling studies indicates 0.80 m height of the initial wave. Subsequently, the results of the tsunami models for both cases were compared and a general assessment of the tsunami hazard in Black Sea Region was provided.
Keywords: Tsunamis -- Turkey.; Tsunamis -- Mathematical models.